Material and Construction Analysis of Double Skin Facade on Universitas Multimedia Nusantara‘s New Media Tower Building - Agara Dama Gaputra (Indonesian Journal of Built Environmental and Sustainability, 2020)
The use of double skin facade in buildings is closely related to the performance of the building concerned. In the application of double skin facade in buildings, the type of material and construction system are some of crucial things that must be considered, especially in the design. This research tries to describe the use of double skin facade through materials and constructions used in UMN's New Media Tower building as an architectural work that successfully utilizes the principle in improving the building's performance. Based on the data obtained, the construction system on a double skin facade uses a hollow aluminium frame that is connected to the main structure of the building for reinforcement, while the double skin facade material use perforated aluminium panels, which is fabricated based on modules with variant dimensions and patterns.double skin facade, construction, material, perforated alumunium